ANALISIS KELAYAKAN USAHA HOME INDUSTRY TEMPE DIMASA PANDEMI COVID-19 DI KELURAHAN SAWAH BREBES (Studi Kasus Pada Home Industry Tempe Bapak M.Sanif) - Sandi, Kurnia; Damayanti, Damayanti; Destalia, Mediya (Jurnal Kompetitif Bisnis, 2023)
ABSTRACT The purpose of this study was to determine and analyze the financial and non-financial viability of Mr. M. Sanif’s tempe home industry during the COVID-19 pandemic. This was a descriptive study that employed a qualitative approach. Observation, interviewing, and documentation were used for data collection. The results show that the financial aspect has a total production cost of Rp. 235.873.000 with a net profit of Rp. 167.327.000. On a nonfinancial level, it operates without a business license; marketing is conducted in the SMEP market through direct sales to consumers; environmental concerns regarding liquid waste management are addressed through the construction of water channels; and solid waste is used as animal feed. On a technical level, the production location is close to the location of theraw materials and sales, themanagement and human resources management divisions have two employees, and regarding social and economic aspects,this industry gives benefit by employingpeople of the surrounding community. The BEP price of rectangular tempe is Rp. 964 with a BEP quantity of 231 pieces, the BEP price of long tempe is Rp. 963 with a BEP quantity of 212 pieces, the R/C Ratio is 1.71, the B/C Ratio is 0.71, the ROI is 65%, the NPV is Rp 534.261.783 and the PI is 3,07%. Thus, the value obtained exceeds the standard eligibility criteria, indicating that Mr. M. Sanif’s tempe home industry is feasible. Keywords: Feasibility